States with Limited Recognition in Russian Foreign Policy: Comparative Analysis of Key Features - V. S. Yagya; I. A. Antonova (Сравнительная политика, 2020)
The main goal of the paper is to reveal, to compare and to summarize the essence of Russian political approaches toward particular cases of states with limited recognition and also to define in global scale whether the stance undergoes transformation or it could be considered as an attitude unique in each special matter when Moscow simultaneously supports independence of South Caucasian Republics and does not recognize Kosovo. The authors believe that there is strong need for Russia of an elaborated strategy based on a robust academic research. The authors outline two de facto approaches to secessionist formations practically applied by contemporary members of international society: international law approach and geopolitical approach. Summing up all the peculiarities of Russian position they assert that Moscow mostly keeps to geopolitical approach towards factual secessions rather international law approach, but in case of Kosovo, Palestine, South Ossetia and Abkhazia it resorts to international law approach. The authors also provisionally divide all contemporary secessionist formations in Russian policy into three groups according to priority ranking and provide results of a detailed content-analysis of Russian foreign policy formal documents and politicians statements that reveal a wide range of appellations concerning secessionist formations. The characteristics testify the fact that Russia strictly keeps to the position of territorial integrity principle respect. Finally, the authors produce two forecasts of further Russian policy towards factual secessions and conclude that Russian policy of consideration each factual secession should continue being individual as fruitful, consistent, deliberate and ensuring more profitable conditions in the context of international cooperation and security.